2006
DOI: 10.1161/01.hyp.0000197952.22711.c4
|View full text |Cite
|
Sign up to set email alerts
|

System y + Arginine Transport and NO Production in Peripheral Blood Mononuclear Cells in Pregnancy and Preeclampsia

Abstract: Abstract-Systemic inflammation and oxidative stress are features of normal pregnancy and, in excess, contribute to the pathogenesis of preeclampsia. Inflammatory cell activation stimulates uptake of arginine (the precursor for nitric oxide) by transport system y ϩ , expression of one of its genes (CAT-2) together with inducible nitric oxide synthase, leading to nitric oxide production. We investigated whether these changes occur in peripheral blood mononuclear cells in normal pregnancy and are exaggerated in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…As reported in undifferentiated cells 29,30 and in differentiated cells such as human peripheral blood mononuclear cells 39,40 or HUVEC, 5 our study suggests functional presence of y + L system in both hEPC-3d and hEPC14d. Remarkably, transport activity associated to this system was about 300 times higher in hEPC-14d compared with 3 days cultured cells.…”
Section: Discussionsupporting
confidence: 85%
“…As reported in undifferentiated cells 29,30 and in differentiated cells such as human peripheral blood mononuclear cells 39,40 or HUVEC, 5 our study suggests functional presence of y + L system in both hEPC-3d and hEPC14d. Remarkably, transport activity associated to this system was about 300 times higher in hEPC-14d compared with 3 days cultured cells.…”
Section: Discussionsupporting
confidence: 85%
“…As reported in undifferentiated cells, 29,30 as well as in differentiated cells such as human peripheral blood mononuclear cells, 39,40 or HUVEC 5 our study suggests functional presence of y + L system in both hEPC-3d and hEPC-14d.…”
Section: A C C E P T E Dsupporting
confidence: 85%
“…Recently, Noris et al 34 suggested that L-arginine depletion, caused by arginase II overexpression, may orient NO synthase toward oxidant species in placenta in preeclampsia. In addition, McCord and colleagues 35 reported that a relative deficiency of arginine in peripheral blood mononuclear cells may favor superoxide and peroxynitrite production and contribute to oxidative and nitrosative stress in preeclampsia. In a study by Conrad and colleagues, 25 under conditions that were carefully monitored to reflect endogenous production and not dietary intake, there was no evidence for a decrease in NO production by measure of plasma or urinary excretion of nitrite and nitrate.…”
Section: Potential Mediators Of Endothelial Dysfunction Nitric Oxidementioning
confidence: 99%